Models of Effective Public Administration in Digitalization - Gul, Jussupova; Dauletbay, Zhussip (Opción, 2019)
The article offers the authors' own vision and understanding of the role of the Digital Proactive Government in order to more effectively influence the central executive, regional and local authorities in addressing issues of social significance via comparative qualitative research methods. As a result, constitutional reform predetermined new conceptual approaches to understanding the main socio-political institutions and the prospects for their development. In conclusion, Gartner experts believe that with the introduction of new technological solutions E-Government does not meet the general trends in digitalization, therefore, the term Digital Government is considered in the maturity assessment model.